Application of Coupling Model of Xin'anjiang River Runoff and TANK Confluence in Southern Humid Area - QIU Wenyi; ZHU Yongjun; ZHAN Zhongyu (Renmin Zhujiang)
In order to improve the accuracy of runoff calculation in humid area of southern China, make full use of hydrological stations of similar basins in nearby or underlying surface to solve the problem of reliability of simulated runoff results in areas without runoff data, and provide reasonable and scientific decision-making basis for construction of water conservancy project at areas without runoff data, this paper proposes the runoff calculation and analysis method combining Xin’anjiang River runoff and TANK confluence, and analyzes the runoff in this area through rainfall and evaporation from 1962 to 2016 by taking Tongshanyuan River Basin as an example. The research calculations show that the basin is mainly controlled by plum rain, its flood season is mainly from April to July, with the runoff accounting for 58.9% of the whole year, and its average runoff depth for many years is 1 198 mm, which can fully reflect the real runoff characteristics of the basin. After comparison and analysis with the 12-year runoff results measured by the Tongshanyuan Hydrological Station, the inter-annual changes of runoff depth are consistent, and the error of runoff results is not more than 2%, so it is believed that the calculation results of the combined runoff analysis method are reasonable, which can not only meet the rationality of the results, but also repair the short board for the lack of hydrological data in the area. Therefore, in areas with abundant precipitation and poor regional hydrological environment, it has better applicability.